FAKTOR-FAKTOR YANG MEMPENGARUHI SKEPTISME PROFESIONAL - Subhan, Subhan (JURNAL AKUNTANSI DAN INVESTASI, 2016)
Regional inspectorate has the task of conducting the general supervision of the local government and other duties assigned by the head of the region, so that the inspectorate duties equal to the internal auditor. This study aims to determine the effect of education, training and experience of the professional skepticism in Sampang District Inspectorate. The independent variables in this study is the level of education, training and experience. The dependent variable in this study is the professional skepticism. The data in this study are primary data obtained from questionnaires circulated to all auditors Inspectorate Sampang. The population in this study are all Inspectorate staff Sampang amounted to 46 employees. Determination of the sample using purposive sampling techniques. The model used in this study using a model of linear regersi beganda. The results showed the level of education, training and experience simultaneously significant effect on professional skepticism in Sampang District Inspectorate. Partially, education and training did not significantly influence the professional skepticism in Sampang District Inspectorate.